Two new species of the genus Astyanax (Characiformes, Characidae) from the Paraná river basin in Argentina - Azpelicueta, María de las Mercedes (2002)
Astyanax leonidas and A. troya are described from the río Paraná basin in northeastern Argentina. Both species share similar number of anal-fin rays and perforated scales in the lateral line, one maxillary tooth, a deep dentary and the presence of small hooks on pectoral, pelvic, anal, and caudal fin of males. These characters are also present in A. ojiara and separate the three species from the remaining species of the genus. Astyanax leonidas is differenciated by the robust body, dorsal profile almost straight, a long and slender maxillary tooth, teeth of premaxillary inner row with notable long central cusp, dentary teeth of similar shape than those of premaxilla, and 4 large dentary teeth followed by one intermediate tooth, and 3 or 4 small teeth. Also this species does not have hooks on dorsal-fin rays and pelvic axillary scale. Astyanax troya has a dorsal profile with marked concavity on supraoccipital area, one broad and low pentacuspid maxillary teeth, teeth of inner premaxillary row gently expanded distally with cusps arising in the same line, central cusp of premaxillary teeth scarcely longer, 8-10 dentary teeth decreasing in size anteroposteriorly, and males with hooks in all fins and pelvic axillary scale.